Maintenance erlotinib versus erlotinib at disease progression in patients with advanced non-small-cell lung cancer who have not progressed following platinum-based chemotherapy (IUNO study). (December 2016) - Cicènas, Saulius; Geater, Sarayut Lucien; Petrov, Petar; Hotko, Yevgeniy; Hooper, Gregory; Xia, Fan; Mudie, Nadejda; Wu, Yi-Long
Highlights: IUNO assessed 1L maintenance vs 2L erlotinib in NSCLC without EGFR mutations. Median OS 9.7 months with 'early erlotinib' vs 9.5 months with 'late erlotinib'. PFS during maintenance treatment was not superior with erlotinib vs placebo. Safety results in IUNO were consistent with the known safety profile of erlotinib. Abstract: Objective: The phase III IUNO trial assessed the benefit of maintenance erlotinib versus erlotinib at progression in advanced/metastatic non-small-cell lung cancer (NSCLC) that had not progressed following four cycles of platinum-based chemotherapy. Materials and Methods: Patients had stage IIIB/IV NSCLC, no known epidermal growth factor receptor ( EGFR) -activating mutation, and objective response or disease stabilization after platinum-based induction chemotherapy. Central EGFR -mutation testing was undertaken on tumors from patients with unknown or wild-type EGFR status following local testing. Patients were randomized to receive blinded maintenance erlotinib 150 mg/day ('early erlotinib') or placebo. Those who progressed on placebo received open-label erlotinib ('late erlotinib'); patients who progressed on erlotinib received approved second-line chemotherapy or best supportive care. Primary endpoint: overall survival (OS). Results: 643 patients were randomized to receive maintenance erlotinib ( n = 322) or placebo ( n = 321). As of March 23, 2015, 242 (75.2%) OS events had occurred with 'early erlotinib' versus 235 (73.2%) with 'late erlotinib'. Median OS was 9.7 and 9.5 months with 'early erlotinib' and 'late erlotinib', respectively (HR, 1.02, 95% CI: 0.85–1.22; log-rank p = 0.82). No progression-free survival, objective response rate, or disease control rate benefit was observed with maintenance erlotinib. 410 patients entered the second-line phase of the study: 160 patients (50%) from the maintenance erlotinib arm and 250 patients (78%) from the maintenance placebo arm. The pattern of adverse events (AEs) was consistent with previous trials; 11 patients who received blinded erlotinib and 3 who received placebo died during the blinded maintenance phase due to nontreatment-related AEs. Conclusions: OS with maintenance erlotinib was not superior to second-line treatment in patients whose tumor did not harbor an EGFR -activating mutation. Safety results were consistent with the established safety profile of erlotinib. Thus, maintenance treatment with erlotinib in patients with advanced/metastatic NSCLC without EGFR -activating mutations is considered unfavorable.